Depression and Associated Factors among Adult Inpatients at Public Hospitals of Harari Regional State, Eastern Ethiopia. (1st April 2018) - Tilahun, Haile; Awoke, Nefsu; Geda, Biftu; Mesfin, Firehiwot
Abstract : Introduction . Globally, depression is one of the three leading causes of disease and it will be the second leading cause of world disability by 2030. The prevalence of depression in Sub-Saharan Africa ranges from 15 to 30%. In Ethiopia, depression was found to be the seventh leading cause of disease burden and its prevalence has been increased in hospital compared to community setting because hospital environment itself is stressful. Yet, no study was done in Eastern Ethiopia, where substance use like Khat is very rampant. Objective . To assess depression and associated factors among adult inpatients at public hospitals of Harari Regional State, Eastern Ethiopia, from February 01 to 28, 2017. Methodology . Hospital based cross-sectional study design was employed on 492 admitted adult patients in Harari region hospitals. Consecutive sampling method was used to include study population. The data were collected by interviewee and analyzed by SPSS version 20.0. Bivariate and multivariate logistic regression analyses were employed.p value of 0.05 or less was considered to be statistically significant. Result . A total of 489 patients were interviewed with response rate of 99.4%. Having duration of 1-2 weeks in the hospital [AOR = 2.02, 95% CI: (1.28, 3.19)], being diagnosed with chronic morbidity [AOR = 4.06, 95% CI: (2.23, 7.40)], being users of psychoactive drugs [AOR = 2.24, 95% CI: (1.18, 4.24)], and having been admitted to surgical ward [AOR = 0.50, 95% CI: (0.31, 0.81)] were significantly associated with depression. Conclusion and Recommendation . Prevalence of depression among admitted inpatients was high. Therefore, increasing the awareness of benefits of early diagnosis of patients to prevent major form of depression and strengthening the clinical set-up and establishing good referral linkage with mental health institutions was considered to be cost-effective method to reduce its prevalence.